2022
DOI: 10.3168/jds.2021-21465
|View full text |Cite
|
Sign up to set email alerts
|

Detailed comparison between organic and conventional milk from Holstein-Friesian dairy herds in Italy

Abstract: Several studies have reported gross composition differences between organic and conventional milk; however, most studies have not considered other factors such as breed and diet ingredients, which are known to influence milk composition. Thus, this study aimed to provide a detailed characterization of Holstein-Friesian cow milk from organic (ORG) and conventional (CONV) herds with similar diet ingredients and in the same geographic area. Bulk milk samples (n = 225) of 12 ORG and 12 CONV farms were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…In the United Kingdom, a case study found that the primary reason for purchasing organic milk is the perceived health benefits, with other important factors being better taste, perceived environmental benefits, and avoiding genetically modified ingredients[ 19 ]. In 2018, organic cow milk production in the European Union accounted for 3.40% of European dairy cows' production, which is double the figure since 2008[ 20 ]. On the other side of the ocean, retail purchases of organic milk products in the United States have increased fivefold since 2002, reaching more than $6 billion in 2020[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, a case study found that the primary reason for purchasing organic milk is the perceived health benefits, with other important factors being better taste, perceived environmental benefits, and avoiding genetically modified ingredients[ 19 ]. In 2018, organic cow milk production in the European Union accounted for 3.40% of European dairy cows' production, which is double the figure since 2008[ 20 ]. On the other side of the ocean, retail purchases of organic milk products in the United States have increased fivefold since 2002, reaching more than $6 billion in 2020[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E is also essential for body functions in both bovines and humans such as growth, reproduction, immunity prevention, and protection of tissues [128]. β-carotene and Vitamin E concentrations differ significantly in raw milk depending on the diet [25]. The dairy industry is interested in a high content of vitamin E and β-carotene, as they can prevent the spontaneous oxidation of milk and fatty acids [129].…”
Section: Vitaminsmentioning
confidence: 99%
“…The concentrations of individual fatty acids in milk fat are affected by factors such as cow breed, stage of lactation, genetics, and diet [113,135]. The composition and quantity of fatty acids in milk are primarily dictated by the feeding system [25,136].…”
Section: Fatsmentioning
confidence: 99%
See 2 more Smart Citations